Validation of Other Distinguishable Varieties (ODV’s) in Rice - K KANAKA DURGA; R ANKAIAH; V BHARATHI (Seed Research, 2026)
Other Distinguishable Variety (ODV) test is mandatory for certain self pollinated crops. Almost all notified seed testing laboratories are conducting the ODV test for genetic purity assessment in field crops. Frequent observation of variations among the STLs in the results of the ODV test warrants declaration of the lots as sub standard leading to huge loss to the producer. In order to find out validity of the ODV test, an experiment was conducted at Seed Research and Technology Center, Rajendranagar, Hyderabad for four consecutive years (2007-08 to 2010-11). Observations recorded on ODV’s based on rejected seed samples revealed variation in seed texture (shape, colour and size of seed) as against authentic breeder seed. Field observations of ODV vis-a-vis control (breeder seed) progenies showed variation in distinguishable morphological DUS characters viz., growth habit, foliage colour, flag leaf curvature, plant height, days to 50% flowering, panicle length and days to maturity. Irrespective of Seed Testing Laboratories, only 56.10% of the seed lots exhibited correctness which may lead to loss to the producer in marketing as substandard lots. The study revealed the requirement of perfect expertise and skill and also training for the seed analysts of APSSCA, APSSDC and NSC in identification of ODV’s in the seed testing laboratories.